2016
DOI: 10.1002/ejoc.201600234
|View full text |Cite
|
Sign up to set email alerts
|

The N‐Hydroxymethyl Group as a Traceless Activating Group for the CAL‐B‐Catalysed Ring Cleavage of β‐Lactams: A Type of Two‐Step Cascade Reaction

Abstract: An efficient enzymatic two-step cascade procedure has been devised for rapid access to diverse amino acids from N-hydroxymethyl--lactams; representative amino acids include the antifungal agent cispentacin, intermediates for the taxol side-chain, and assorted cathepsin inhibitors. When CAL-B-catalysed hydrolyses of racemic N-hydroxymethyl--lactams were performed with H 2 O (0.5 equiv.) in iPr 2 O at 60°C, relatively quick (vs. non-activated counterparts) and enantioselective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In further studies, we have probed our very recent results found about the ring cleavage of specially activated lactams [ 28 ], where the activating group underwent to a traceless, in situ degradation. Accordingly, the ring cleavage of (±)- 4 was attempted with H 2 O in the presence of CAL-B and benzylamine to capture formaldehyde in i Pr 2 O at 60 °C ( Scheme 4 , Table 2 , entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In further studies, we have probed our very recent results found about the ring cleavage of specially activated lactams [ 28 ], where the activating group underwent to a traceless, in situ degradation. Accordingly, the ring cleavage of (±)- 4 was attempted with H 2 O in the presence of CAL-B and benzylamine to capture formaldehyde in i Pr 2 O at 60 °C ( Scheme 4 , Table 2 , entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…In view of earlier results on enzymatic acylation of N -hydroxymethyl eight-membered carbocyclic β-lactams [ 4 , 24 ], we first planned to carry out enzymatic acylation of N -hydroymethyl-9-azabicyclo[6.2.0]dec-6-en-10-one [(±)- 4 ] ( Figure 1 ). The extensive investigations of the lipase-catalyzed ring cleavage of unactivated [ 25 , 26 , 27 ] and activated [ 28 ] β-lactams then suggested the possibility of the lipase-catalyzed enantioselective ring cleavage of racemic unactivated 9-azabicyclo[6.2.0]dec-6-en-10-one [(±)- 3 ] and activated (±)- 4 and N -hydroxymethyl 9-azabicyclo[6.2.0]dec-4-en-10-one [(±)- 6 ]. A systematic comparison of the efficiency of these methods, with regard to E , reaction rate and yield for the products, was also intended.…”
Section: Introductionmentioning
confidence: 99%
“…They are useful starting materials for further synthetic transformations and used for the preparation of a set of valuable molecular systems such as amino acids, alkaloids, amino alcohols or heterocycles . The high synthetic value of this type of derivatives is demonstrated by the syntheses and applications of functionalized β‐lactams or some fused bicyclic β‐lactams . For example, opening of the azetidinone ring of various β‐lactam derivatives is considered to be one of the most convenient pathways for the stereocontrolled synthesis of open‐chain or cyclic β 2,3 ‐amino acid derivatives .…”
Section: Introductionmentioning
confidence: 99%